Oral Hygiene Habits and Knowledge Among Dentistry Students and Patients: A Questionnaire Study - Tuğba Şahin (European Annals of Dental Sciences)

(untitled)
Purpose: This study aimed to the compare oral hygiene habits, awareness, and knowledge dental students and patients. Materials & Methods: This study was conducted at Xxx University, Faculty of Dentistry. The study included 266 participants divided into groups of dental students (n=127) and patients (n=127). A structured questionnaire with 65 multiple-choice questions covering demographic information, oral hygiene habits, awareness, and knowledge about dental care was used. All the statistical analyses, including chi-square tests and independent sample t-tests, were performed using IBM SPSS Statistics (version 26.0). Results: There were significant differences in tooth brushing frequency, time and toothpaste type, tooth brushing technique, product they used for dentures, and frequency of toothbrush replacement between dental students and patients (p